A diecast mineralization process forms the tough mantis shrimp dactyl club - Amini, Shahrouz (2021)
Biomineralization, the process by which mineralized tissues grow and harden via biogenic mineral deposition, is a relatively lengthy process in many mineral-producing organisms, resulting in challenges to study the growth and biomineralization of complex hard mineralized tissues. Arthropods are ideal model organisms to study biomineralization because they regularly molt their exoskeletons and grow new ones in a relatively fast timescale, providing opportunities to track mineralization of entire tissues. Here, we monitored the biomineralization of the mantis shrimp dactyl club—a model bioapatite-based mineralized structure with exceptional mechanical properties—immediately after ecdysis until the formation of the fully functional club and unveil an unusual development mechanism. A flexible membrane initially folded within the club cavity expands to form the new club’s envelope. Mineralization proceeds inwards by mineral deposition from this membrane, which contains proteins regulating mineralization. Building a transcriptome of the club tissue and probing it with proteomic data, we identified and sequenced Club Mineralization Protein 1 (CMP-1), an abundant mildly phosphorylated protein from the flexible membrane suggested to be involved in calcium phosphate mineralization of the club, as indicated by in vitro studies using recombinant CMP-1. This work provides a comprehensive picture of the development of a complex hard tissue, from the secretion of its organic macromolecular template to the formation of the fully functional club.